Consistency Examination of a Systematic Review and Data Analysis Report for a Social Justice Study—A Mixed Research Model (Journal of Education and Development, 2023)
This study aimed to investigate an approach for assessing the quality of doctoral dissertations, specifically focusing on the consistency between essential elements, namely the literature review and quantitative analysis results. To accomplish this, a mixed-methods design was employed. The qualitative data were analyzed using semantic network and thematic analysis techniques, while the quantitative data were processed using SPSS procedures. The study's findings demonstrated that this mixed-methods model effectively facilitates the examination of dissertation quality and consistency among key elements, such as the literature review and data analysis results. By integrating qualitative and quantitative approaches, researchers gain a comprehensive understanding of the dissertation's quality and the alignment between its different components.